A study in the entrepreneurial characteristics of university students - Yeap, Yong Ai (2002)
The title of this research is "A Study in the Entrepreneurial Characteristics of University Students" is aimed to find out the entrepreneurial characteristics of students who are entrepreneurial inclined. In this research the six entrepreneurial characteristics: risk propensity, self-confident, need for achievement, innovation, tolerance of ambiguity, and locus of control became the primary interested variables. The null hypothesis of this research studied that who are entrepreneurial inclined have the level of entrepreneurial characteristics which are not the same level as those who are non-entrepreneurial inclined. The results will be discussed from marketing perspective. 300 undergraduate students from Universiti Putra Malaysia, Universiti Kebangsaan Malaysia, and Universiti Malaya were selected to answer a set of questionnaire. The result showed that, Malaysian university students who are entrepreneurial inclined have the levels of risk propensity, self-confident, innovation and need for achievement which are higher than those who are non-entrepreneurial inclined.